Sledeč nosu - Howes, David (Amfiteater (Ljubljana), 2021)
The essay examines and comments on the new dawn for smell research that vindicates the efforts of scholars and artists across a range of disciplines, such as Barabara Pia Jenič in theatre studies and Asifa Majid in anthropological linguistics, to put smell on the map. The author explores why it has taken so long for smell to come into its own by reviewing some of the highly prejudicial treatment this sense has garnered in the past. The author links this new phenomenon with the history of theoretical thoughts and concepts of smell within Western cultures.
Keywords: antropologija vonja; antropology of smell; estetika; raziskave vonjav; sensorial researches; sensorial theatre; senzorialne zaznave; senzorialno gledališče; theatre studies; theory of smell